Micromorphology and dielectric properties of epoxy matrixed composites with different carbon materials. (27th July 2019) - Wang, Jihua; Han, Zhidong; Jin, Yang; Wang, Yongliang
Abstract: Graphene nanoplatelets (GNPS) was prepared by oxidation coupled mechanical delamination method. Epoxy based composites were prepared with GNPS, carbon black (CB) and graphite nanopowders (nanoG). The dispersion of different carbon materials was investigated by scanning electron microscope (SEM), which showed the better compatibility of GNPS in epoxy matrix. The results of dynamic mechanical thermal analysis (DMTA) showed the lower glass transition temperature (Tg) of GNPS/epoxy composite, indicating the influence of GNPS on the curing of epoxy resin. The higher storage modulus of GNPS/epoxy composite was the evidence of its better compatibility. The dielectric behaviors of the composites were studied in a wide frequency range. The GNPS/epoxy composite showed high dielectric permittivity and loss at low frequency due to its interfacial polarization. The composites with 1.0 wt.% GNPS presented much higher dielectric permittivity at high frequency.